Helicobacter pylori cagA+ Is Associated with Milder Duodenal Histological Changes in Chilean Celiac Patients - Lucero, Yalda; Oyarzún, Amaya; O'Ryan, Miguel; Quera, Rodrigo; Espinosa, Nelly; Valenzuela, Romina; Simian, Daniela; Alcalde, Elisa; Arce, Claudio; Farfán, Mauricio J.; Vergara, Alejandra F.; Gajardo, Iván; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Background: Mechanisms underlying the high clinical and histological diversity of celiac disease (CD) remain elusive. Helicobacter pylori (Hp) chronically infects gastric and duodenal mucosa and has been associated with protection against some immune-mediated conditions, but its role (specifically of cagA+ strains) in CD is unclear. Objective: To assess the relationship between gastric Hp infection (cagA+ strains) and duodenal histological damage in patients with CD. Design: Case-control study including patients with active-CD, potential-CD and non-celiac individuals. Clinical presentation, HLA genotype, Hp/cagA gene detection in gastric mucosa, duodenal histology, Foxp3 positive cells and TGF-β expression in duodenal lamina propria were analyzed. Results: We recruited 116 patients, 29 active-CD, 37 potential-CD and 50 non-CD controls. Hp detection was similar in the 3 groups ( 30-40%), but cagA+ strains were more common in infected potential-CD than in active-CD (10/11 vs. 4/10; p=0.020) and non-CD (10/20; p=0.025). Among active-CD patients, Foxp3 positivity was significantly higher in subjects with cagA+ Hp+ compared to cagA- Hp+ (p<0.01) and Hp- (p<0.01). In cagA+ Hp+ individuals, Foxp3 positivity was also higher comparing active- to potential-CD (p<0.01). TGF-β expression in duodenum was similar in active-CD with cagA+ Hp+ compared to Hp- and was significantly downregulated in cagA+ potential-CD subjects compared to other groups. Conclusion: Hp infection rates were similar among individuals with/without CD, but infection with cagA+ strains was associated with milder histological damage in celiac patients infected by Hp, and in active-CD cases with higher expression of T-reg markers. Results suggest that infection by cagA+ Hp may be protective for CD progression, or conversely, that these strains are prone to colonize intestinal mucosa with less severe damage.